2003
DOI: 10.1152/jn.00562.2002
|View full text |Cite
|
Sign up to set email alerts
|

Preparatory Set Associated With Pro-Saccades and Anti-Saccades in Humans Investigated With Event-Related fMRI

Abstract: . Preparatory set associated with pro-saccades and anti-saccades in humans investigated with event-related fMRI. J Neurophysiol 89: 1016 -1023, 2003. First published October 30, 2002 10.1152/jn.00562.2002. Previous studies have shown that the BOLD functional MRI (fMRI) signal is increased in several cortical areas when subjects perform anti-saccades compared with pro-saccades. It remains unknown, however, whether this increase is due to an increased cortical motor signal for anti-saccades or due to difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
200
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(236 citation statements)
references
References 33 publications
34
200
2
Order By: Relevance
“…This is important because low levels of baseline activity were predictive of errors (Fig. S6), as found in other studies (40), and because baseline activity is likely related to response preparation, which has been identified as a critical parameter for the developmental improvement of inhibitory control (41,42). Baseline activity in our data may represent preparation for the task by virtue of representing the task rules ahead of the stimulus presentation.…”
Section: Discussionsupporting
confidence: 73%
“…This is important because low levels of baseline activity were predictive of errors (Fig. S6), as found in other studies (40), and because baseline activity is likely related to response preparation, which has been identified as a critical parameter for the developmental improvement of inhibitory control (41,42). Baseline activity in our data may represent preparation for the task by virtue of representing the task rules ahead of the stimulus presentation.…”
Section: Discussionsupporting
confidence: 73%
“…The right dentate nucleus was also more active, suggesting increased activity in cerebello-thalamic circuitry as well as frontostriatal systems. Regions in this frontostriatal and cerebello-thalamic circuitry are typically involved in the execution of intentional behaviors based on internalized representations and cognitive plans rather than automatic responses to external sensory stimuli (Sweeney et al, 1996;DeSouza et al, 2003;Nitschke et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This could account for the greater dependence on the rostral frontostriatal pathways that are known to support saccades made on the basis of internally generated plans (Sweeney et al, 1996;DeSouza et al, 2003;Nitschke et al, 2004). However, when saccades are based on voluntary decisions, response latencies increase considerably relative to reflexive saccades, typically by more than 100 ms, in both typically developing individuals and individuals with autism (Munoz et al, 1998;Luna et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…DeSouza, Menon, and Everling (2003) found that activation within the dorsolateral prefrontal cortex was evident following the presentation of a cue stimulus that instructed viewers to either make a pro-or antisaccade in response to the target onset.…”
Section: Age-related Impairments In Inhibitionmentioning
confidence: 99%